ANALISIS TINGKAT KESADARAN MASYARAKAT TERHADAP BAHAYA CYBERCRIME (STUDI KASUS KECAMATAN JATIYOSO) - Miswanto, Miswanto (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
In the digital era, the use of the internet and technology is increasingly widespread. The urgency of this research is the number of public complaints related to cybercrime cases, so the protection of personal data and cybersecurity is very important. protection of personal data and cybersecurity is very important. Public awareness of the potential this risk is key to protecting their personal and financial information. Awareness aware-ness of the types of cybercrime and the actions they can take to prevent them can help reduce incidents of cybercrime. prevent it can help reduce the incidence of cybercrime. Knowledge and awareness aware-ness of cybercrime is the first step in preparing themselves to deal with increasingly complex digital threat. This research aims to understand the extent to which people in the region have an awareness of the potential dangers faced from cybercrime, including an understanding of the types of cybercrime they may face. In addition, it can identify factors that may affect the level of public awareness of the dangers of cybercrime, such as age, education, internet access, or previous experience. The research was conducted at the Jatiyoso sub-district level which consists of 9 villages. So as to obtain 135 respondents who filled out the Pre-Test and Post-Test Questionnaire from the criteria of adults aged 17 - 40 years and identify factors that contribute to the level of awareness about cybercrime, including demographic data analysis. Then, it can help local communities to better understand the threat of cybercrime, so that they always protect their personal data and contribute to cyber safety in the Jatiyoso sub-district area. Similarly, it can provide recommendations to the local government or related institutions such as schools, and community organizations to increase community awareness of the dangers of cybercrime. organizations to increase public awareness of the dangers of cybercrime through education or awareness programs. educational or awareness programs.